Reliability assessment of fire safety systems in railway industry: a case study - Kaymakci, Ozgur Turay; Ustoglu, Ilker; Divriklioglu, Ender (CHINESE INST ENGINEERS, 2015)
Within the framework of railroad transportation systems, there are currently system rooms where critical systems such as signalization are available. For the system to achieve an uninterrupted mode of operation, it is crucial to mitigate risks or hazards against the rooms and to ensure an acceptable level of safety. This study handles the protection of a system room, owned by Istanbul Ulam A.S. Edirnekap branch, against an incident of fire as a safety-related system practice. Within this scope, the fire safety system has been handled as a safety-related system identified in IEC 61508. The safety integrity level required by the safety lifecycle for the relevant system has also been identified and safety functions that are required to be implemented have been put forth. Taking IEC 61508 as a reference for the functions, the required analyses have been performed through fault tree analysis. It has also been guaranteed that the relevant functions have met the required safety levels.
Keywords: railway systems; fire; functional safety; Engineering